Introduction to the systematics and biodiversity of eels (orders Anguilliformes and Saccopharyngiformes) of Taiwan - Ho, Hsuan-Ching; Mccosker, John E.; Smith, David G.; Shao, Kwang-Tsao (Zootaxa, 2015)
The eel fauna (orders Anguilliformes and Saccopharyngiformes) of Taiwan is one of the richest in the world. Recent genetic and morphological studies have improved the taxonomic resolution and increased the known diversity of the eels of Taiwan, and the overall diversity is comparable to that of adjacent marine zoogeographic regions with rich biodiversity, such as Australia and the Philippines. In this special issue, we verified the historical records and examined numerous recently collected specimens, and conclude that the eel fauna of Taiwan is represented by 207 species in 75 genera and 14 families, with several undescribed species still likely to be discovered. The Muraenidae (71 species), Ophichthidae (60), Congridae (29) and Synaphobranchidae (17) are the most abundant and species-rich in Taiwanese waters. We add 42 species to the Taiwanese fish fauna, including one new genus and 13 new species. Two further species are newly described, one from the Philippines and one from Indonesia.